Signifikansi Literasi Keuangan terhadap Pengguna Aktual Dompet Digital - Karsono, Lorena Dara Putri; Salma, Laila Fairuz (Universitas Islam Negeri Sunan Kudus, 2022)
AbstractThe emergence of many conveniences in using digital wallets are the goal in this study, namely to determine the effect of the three components of financial literacy on the financial satisfaction of digital wallet users in Generation Z. The three components of financial literacy consist of financial behaviour, financial attitude and financial knowledge. This study uses a quantitative descriptive analysis method, with purposive sampling method for determining the population that consist of 40,000 ShopeePay Indonesia Twitter account followers and a sample of 380 ShopeePay Indonesia Twitter account followers. Data collection techniques use literature and questionnaires with Likert scale techniques. The analysis technique in this study uses multiple linear regression analysis with SPSS 24 software tools for windows. The results showed that the financial behaviour variable (X1) had no partial effect on financial satisfaction. While the variables of financial attitude (X2) and financial knowledge (X3) have partial effect on financial satisfaction. The variables of financial behaviour, financial attitude, and financial knowledge simultaneously affect the financial satisfaction of Shopeepay digital wallet users in Generation Z. Therefore, there are need a development in this research and can be used as theoretical support, especially in the financial literacy component.Keywords: financial literacy, financial behaviour, financial attitude, financial knowledge, financial satisfaction